COMPARATIVE STUDY ON VITALITY PRESERVATION OF YOUNG PERMANENT TEETH USING BIOACTIVE MATERIALS - Liana Aminov; Mihaela Salceanu; Tudor Hamburda; Cristian Giuroiu; Maria Vataman (Romanian Society of Oral Rehabilitation, 2014)
Introduction Traumatic injuries and decays are the biggest challenges to the integrity of a young permanent tooth .The aim of this study was to compare the biostimulating and repairing action of mineral trioxide aggregate (MTA) and of the mineral aggregate with ceramic nanoparticles (BioAgreggate) with calcium hydroxide action, in terms of clinical-radiological parameters, after vital pulp therapy in young permanent teeth affected by dental caries or traumatic injury. Material and methods The study was conducted on a sample of 36 teeth from 31 patients of both sexes, aged between 7 and 15 years (mean 9.3 ± 1.9 years), divided into three groups, and took place for a period of up to 4 years. Results The results concerning the effectiveness of the three materials used were evaluated in terms of clinical and radiological manifestations. These were significantly correlated (Ȥ2 = 35.3, r = 0.705, p = 0.003, 95% CI), the study demonstrating an important differences between the three groups of teeth. Final evaluation showed a significant association (Ȥ2 = 18.69, r = 0.725, p = 0.001, 95% CI) between the material used and the final results. Conclusions Following clinical aseptic procedures, after removing bacterial contamination, applying a bio-stimulative dressing and an hermetic crown sealing, there are high chances (about 95%) that the pulp of a young permanent tooth, even seeming irreversibly inflamed, to return to the original status and continue to exercise its functions with longterm preservation of vitality.